Temperature dependence of the transient characteristics in NPT IGBT using linear and parabolic model - Tania, Shoulin; Saha, Dipraj; Faiza, Fahmida (BRAC University, 2017)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2016.